The Relationship Of Hormonal Contraception Use With Menopause Age In Environment V Of New Kelurahan Bambu Field Of Winning Field - Sari Rahma Fitri; Nurdiana Manurung (Institute of Computer Science (IOCS), 2020)
One of the factors that affect the age of menopause is the use of contraception where the decrease in levels of the hormones estrogen and progesterone causes respondents to experience menopause symptoms at the age of more than 50 years. This study aims to determine the relationship between the use of hormonal contraception and menopause age in the V Village of Baru Ladang Bambu, Medan Tuntungan District. The research method used isanalytical quantitativewith a cross sectional approach. The population in this study were postmenopausal women in Neighborhood V, Baru Ladang Bambu Village, Medan Tuntungan District, amounting to 70 people. The sampling technique is accidental sampling. The sample in this study was all postmenopausal women, a total of 70 menopausal women in Neighborhood V of Kelurahan Baru Ladang Bambu, Medan Tuntungan Subdistrict in 2020. Based on the results of the study, it was found that the use of hormonal contraception experienced a late menopause 77.1%. The results of the chi square statistical test are obtainedp = 0.342,this means that the value of p is greater than the value of and thus Ho is accepted and Ha is rejected.It is hoped that health workers will continue to provide counseling about the use of hormonal contraception.